Alcohol-Induced Liver Injury Is Modulated by Nlrp3 and Nlrc4 Inflammasomes in Mice. (16th December 2013) - DeSantis, David A.; Ko, Chih-wei; Liu, Yang; Liu, Xiuli; Hise, Amy G.; Nunez, Gabriel; Croniger, Colleen M.
Abstract : Alcoholic liver disease (ALD) is characterized by increased hepatic lipid accumulation (steatosis) and inflammation with increased expression of proinflammatory cytokines. Two of these cytokines, interleukin-1 β (IL-1 β ) and IL-18, require activation of caspase-1 via members of the NOD-like receptor (NLR) family. These NLRs form an inflammasome that is activated by pathogens and signals released through local tissue injury or death. NLR family pyrin domain containing 3 (Nlrp3) and NLR family CARD domain containing protein 4 (Nlrc4) have been studied minimally for their role in the development of ALD. Using mice with gene targeted deletions for Nlrp3 (Nlrp3 −/− ) and Nlrc4 (Nlrc4 −/− ), we analyzed the response to chronic alcohol consumption. We found that Nlrp3 −/− mice have more severe liver injury with higher plasma alanine aminotransferase (ALT) levels, increased activation of IL-18, and reduced activation of IL-1B. In contrast, the Nlrc4 −/− mice had similar alcohol-induced liver injury compared to C57BL/6J (B6) mice but had greatly reduced activation of IL-1 β . This suggests that Nlrp3 and Nlrc4 inflammasomes activate IL-1 β and IL-18 via caspase-1 in a differential manner. We conclude that the Nlrp3 inflammasome is protective during alcohol-induced liver injury.